Students’ Expectationon Speaking Subject During The Covid-19 Pandemic In The Second Semester at Muhammadiyah University of Parepare - Ilham, Ilham (Pusat Pengembangan Publikasi dan Hak Kekayaan Intelektual Universitas Muhammadiyah Parepare, 2023)
Covid-19 situation changes the educational context a lot, the learning process was conducted online. Yet, post Covid-19 pandemic conditions change again the learning context. This research was conducted to know the students’ expectation on speaking learning. In particular, this research aims to find out why the student expects speaking lessons to be offline learning, what the students expect of an offline speaking learning during the pandemic Covid-19 era, and what obstacles students face during online learning so they want to do an offline speaking learning. This research used qualitative descriptive design. The research instruments were observation and interview. In analysis the data, the pattern of Miles and Huberman was implemented. The research subject was 10 students of English department at Muhammadiyah University of Parepare. The students want to study offline because they face many obstacle in learning English using online learning. In learning speaking, students face many obstacles such as lack of communication due to poor network, often disturbing learning atmosphere, too much time or not being on time, and lack of direct interaction. This is what can affect learning outcomes and reduce student learning motivation. To sum up, the students have high expectation for offline learning in speaking subject.